Dominant Forms of Livelihood Adaptation and Key Constraints in Mantuil Village, Banjarmasin City - Ikhlasul Rahman, Mizan; Maulidyawati, Septy (Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
Livelihood analysis involves perceptions and complexities, as it encompasses a bottom-up approach and is context-dependent, focusing on individuals, households, communities, and social groups. Furthermore, livelihood adaptation is crucial to cope with various risks and shocks, which pose a greater threat for vulnerable residents living in a slum area. This analysis attempts to understand the forms of livelihood adaptation and constraints within the area. This understanding also contributes to a valuable discussion on livelihood and better interventions. The Garrett’s ranking is employed to identify and analyze these forms and constraints. The dominant adaptation forms involve job seeking, land and tools utilization, counting on family support, and increasing societal concern for others. The key constraints comprise limited job opportunities, inequality, damaged infrastructure, inappropriate social assistance, and uncertain natural disruption. Both adaptation forms and constraints are interconnected, and resolving constraints is needed to facilitate effective adaptation.